Advanced analysis of motor development - Haywood, K. M.; Roberton, M. A.; Getchell, N. (Human Kinetics, 2012)
Advanced Analysis of Motor Development explores how research is conducted in testing major issues and questions in motor development. It also looks at the evolution of research in the field, its current status, and possible future directions. This text is one of the few to examine motor development models and theories analytically while providing a context for advanced students in motor development so they can understand current and classic research in the field.